Hemp globulin forms colloidal nanocomplexes with sodium caseinate during pH-cycling. (December 2021) - Chuang, Chih-Chieh; Ye, Aiqian; Anema, Skelte G.; Loveday, Simon M.
Graphical abstract: Highlights: Solubility of hemp globulin increased (≈20% to > 80%) after pH-cycling with caseinate. Monodisperse nanoparticles (≈ 130 nm) made of hemp globulin and caseins were created. The nanoparticles dissociated between 40 and 60 °C and aggregated above 60 °C. The nanoparticles were quite heat-stable, Z-average ≈ 230 nm after 30 min at 90 °C. N-ethylmaleimide blocked free thiol groups and resulted in bimodal size distribution. Abstract: Seed from industrial hemp ( Cannabis sativa L.) contains around 25% protein (mainly globulins) which is easily digested, but the low solubility of hemp globulins (HG) limits their application in many food systems. In this study, the solubility of HG was improved by blending HG with sodium caseinate (SC) and treating with a pH-cycling process. The pH-cycling involved adjusting the pH to 12 and reacting for 1 hr, followed by neutralisation to pH 7. Nanoparticles composed of HG and SC (Z-average diameter ≈ 130 nm) were formed after the pH-cycling, and the solubility of HG increased to > 80% when there was more than 1% of SC for 1% of HG. These HG|SC nanoparticles were monodisperse (PDI < 0.17) and ζ-potential was ≈ −17 mV. Hydrogen bonding is the main forces that assembles HG|SC nanoparticles because the nanoparticles dissociated by heat treatment (up to 60 °C) or urea, which is an effective hydrogen bond breaker. HG|SC nanoparticles will aggregate irreversibly above 60 °C, possibly due to thiol-disulphide exchange. The nanoparticles were heat-stable as the Z-average diameter was only 229 nm after heating (90 °C, 30 min). N-ethylmaleimide blocked free thiol groups on HG and resulted in less disulphide-linked HG aggregation after pH- cycling, which in turn lead to smaller HG|SC nanoparticles and a bimodal particle size distribution, indicating the importance of disulphide bond for the formation of monodisperse HG|SC nanoparticles. The soluble and heat-stable HG|SC nanoparticles could be used to increase the hemp protein content in beverages and emulsions.